Neural correlates of religious behavior related to Christianity: an ALE meta-analysis - Yeung, Andy Wai Kan; Wong, Natalie Sui Miu; Tsui, Ice S. Y.; Lee, Terence C. P. (Frontiers in Psychology, 2025)
BackgroundMultiple neuroimaging studies have been published to report brain processing of religious behavior related to Christianity, such as prayer and recitation of the Bible. This meta-analysis aimed to pool data across studies to identify brain regions consistently activated in response to such religious tasks.MethodsWeb of Science, Scopus, and PubMed were queried to identify relevant studies. Brain coordinates and sample size were manually extracted from the identified studies, and entered into a dedicated software called GingerALE to conduct meta-analysis.ResultsMeta-analytic results based on 11 studies showed that brain processing of Christian behavior was associated with the right middle frontal gyrus and superior frontal gyrus, with a peak location (at 44, 38, 26; cluster size = 760 mm3) preferentially associated with working memory, cognitive task, and executive function according to Neurosynth data. Sub-analyses on Christian subject data revealed no significant results at the pre-defined threshold. With a more liberal threshold, Christian tasks > non-Christian tasks showed activation in the anterior cingulate and medial frontal gyrus (peak at 4, 48, −4; cluster size = 256 mm3) that were frequently associated with reward, self-referential, and reinforcement learning, whereas non-Christian tasks > Christian tasks showed activation in the right middle frontal gyrus (peak at 48, 36, 24; cluster size = 472 mm3) that frequently associated with working memory, executive function, arithmetic, and calculation.ConclusionThis study has revealed the relevance of frontal and limbic regions to Christian behavior.